PERSEPSI MASYARAKAT TERHADAP KONFLIK MACAN TUTUL JAWA DENGAN WARGA SEKITAR SUAKA MARGASATWA GUNUNG SAWAL - Andina Agustia Dewanti; Hero Marhaento (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2021)
Mount Sawal Wildlife Reserve is known as one of the places that has the highest number of conflict cases between Javan leopard and human in Indonesia. There were 38 conflict cases recorded in the period of 2001-2016 with the highest number of cases occurring in Kertamandala and Cikupa Villages, Ciamis District, West Java. This study assessed the community perception of those two villages towards the conflict by using Q-method in combination with the R-Studio statistics to analyze the data. There were 19 participants who were tested with 16 consent statements called Q-sorting were ranked based on approval scale. The results showed that the community perceptions of conflict can be grouped into three, namely: 1) the importance to preserve the existence of javan leopards, 2) wildlife conflict management is a shared responsibility between communities and authorities, and 3) in the future, wildlife conflicts must not take place again. In addition, all participants shared consensus that the community do not accept the existence of javan leopard in their village area and they also agreed that conservation authorities have taken actions to deal with the conflict.